Nationwide Distribution of Culex Mosquitoes and Associated Habitat Characteristics at Residential Areas in Malaysia - Low, V.L.; Chen, C.D.; Lee, H.L.; Lim, P.E.; Leong, C.S.; Sofian-Azirun, Mohd (2012)
A standardized larval dipping method was used to determine the infestation rates of Culex and other species of mosquitoes in stagnant water at 20 residential areas. This study also examined the associations between Culex distribution and various habitat characteristics across all states in Malaysia. Identification of 7,848 specimens yielded 6 species dominated by Culex quinquefasciatus (82.74), followed by Cx. vishui (14.39), Cx. gelidus (2.70), Lutzia fuscanus (0.11), Armigeres subalbatus (0.05), and Anopheles separatus (0.01). The Culex larvae occurred in stagnant water with pH ranging from 6.4 to 8.2; conductivity, 139.7 to 6635.2 s/cm; salinity, 0.07 to 3.64 ppt; total dissolved solids, 0.09 to 4.27g/liter; and dissolved oxygen, 5.11 to 8.11 mg/liter. The mean number of Culex larvae was positively correlated with pH, conductivity, salinity, and total dissolved solids. In contrast, the elevation and dissolved oxygen were found negatively correlated with mean number of Culex larvae. This study documented baseline information on the habitat characteristics of Culex species for the 1st time at different residential areas in Malaysia. The findings of this study will be a timely reminder to local authorities that effective control measures should be monitored regularly in order to reduce the nuisance of these mosquitoes and the risks of disease transmission. Â© 2012 by The American Mosquito Control Association, Inc.